High-efficiency anaerobic co-digestion of food waste and mature leachate using expanded granular sludge blanket reactor - Liu, Yanxu; Lv, Yuanyuan; Cheng, Hui; Zou, Lianpei; Li, Yu-You; Liu, Jianyong (Bioresource Technology, 2022)
[Display omitted] •AcoD of FW and mature leachate was performed in an EGSB reactor for the first time.•High CH4 yield and OLR (5.87 L/L/d, 23.6 g COD/L/d) from FW were achieved by AcoD.•NH4+-N, TMs in leachate improved four-stage rates with excellent AD performance.•Dominant genus changed from AM to HM with OLR increase, resisting acid impact. Anaerobic digestion of food waste receives more and more attention for waste-to-energy conversion, while easy acidification and limited efficiency hinder its wide application. To improve anaerobic digestion of food waste, its anaerobic co-digestion with mature leachate was performed using an expanded granular sludge blanket reactor. With the chemical oxidation demand (COD) removal of around 80%, the methane production and organic loading rate of the reactor reached 5.87 ± 0.45 L/L/d and 23.6 g COD/L/d, respectively. The rate of COD converted to methane was ranging from 74% to 87%. The addition of mature leachate provided ammonium to avoid acidification and trace metals for microbial growth, and the efficiencies of four stages of anaerobic digestion were all enhanced. The predominant methanogenic genera were shifted to adapt the changing condition, thus stabilizing the system. These findings support high-efficiency bioenergy recovery from food waste and leachate in practice.